2021
DOI: 10.3389/fmicb.2021.726878
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Growth Performance, Intestinal Morphology, and Microbiota Composition and Metabolism in Mice

Abstract: BackgroundResveratrol (RSV) plays a vital role in alleviating various stresses and improving intestinal health. The current study was conducted to explore whether RSV alleviates weaning stress through improving gut health in a weaning mouse model. Forty 21-day-old weaned mice were randomly assigned to a control group without RSV treatment and three treatment groups with 10, 20, and 50 mg/kg RSV for 28 days.ResultsThe results showed that RSV at a dose of 20 mg/kg improved total body weight, intestinal morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Consistently, in the present study, we observed that the heat stress environment (35 ± 2 °C) reduced the average daily feed intake of broilers by 31.85–50.17% and decreased the average daily weight gain by 25.74–44.29%. Similar to a recent finding showing that dietary antioxidants improved the growth performance of weaned mice [ 33 ], the present study revealed that dietary EA at a dose of 75 and 150 mg/kg increased the final weight gain of the heat-stressed 14-day-old broilers by 8.70–9.91% under HS. Energy is shifted from the production system to the protection strategy against heat stress in heat-stressed birds [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, in the present study, we observed that the heat stress environment (35 ± 2 °C) reduced the average daily feed intake of broilers by 31.85–50.17% and decreased the average daily weight gain by 25.74–44.29%. Similar to a recent finding showing that dietary antioxidants improved the growth performance of weaned mice [ 33 ], the present study revealed that dietary EA at a dose of 75 and 150 mg/kg increased the final weight gain of the heat-stressed 14-day-old broilers by 8.70–9.91% under HS. Energy is shifted from the production system to the protection strategy against heat stress in heat-stressed birds [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…We found that the addition of RES could increase the villus height, and alleviate the intestinal morphological damages induced by LPS, thus improving the intestinal mucosa integrity in yellow-feathered broilers. These results are consistent with previous studies on the protective effect of RES on intestinal morphology and structure ( Liu et al, 2016 ; Zhuang et al, 2021 ; Hong et al, 2022 ). Moreover, the intestine mucosal barrier represents the first line of the host defence against invading enteric pathogens and toxins, which plays key roles in nutrient digestion and absorption ( Turner, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…The change in the balance of dominant flora may be related to aggravation of nasal inflammation caused by vancomycin intervention. nutrients by breaking down host intestinal dietary cellulose, is one of the bacteria that produce SCFAs, and stabilizes the intestinal barrier, thus alleviating allergic diseases (Tun et al, 2017;Zhuang et al, 2021). This study found a significant decrease in Ruminococcus following gut microbiota dysbiosis and a significant, negative correlation in fecal SCFAs, suggesting that vancomycin-induced gut microbiota In contrast, the increased floras in the Van group, such as Escherichia-Shigella and Klebsiella, were significantly negatively correlated with SCFAs in feces.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcus plays a crucial role in metabolism. It obtains nutrients by breaking down host intestinal dietary cellulose, is one of the bacteria that produce SCFAs, and stabilizes the intestinal barrier, thus alleviating allergic diseases ( Tun et al, 2017 ; Zhuang et al, 2021 ). This study found a significant decrease in Ruminococcus following gut microbiota dysbiosis and a significant, negative correlation in fecal SCFAs, suggesting that vancomycin-induced gut microbiota dysbiosis may aggravate AR by decreasing Ruminococcus and subsequently decreasing SCFAs.…”
Section: Discussionmentioning
confidence: 99%